Effects of One Resistance Exercise Session on Vascular Smooth Muscle of Hypertensive Rats - Silva,Tharciano Luiz Teixeira Braga da (2015)
Abstract Background: Hypertension is a public health problem and increases the incidence of cardiovascular diseases. Objective: To evaluate the effects of a resistance exercise session on the contractile and relaxing mechanisms of vascular smooth muscle in mesenteric arteries of NG-nitro L-arginine methyl ester (L-NAME)-induced hypertensive rats. Methods: Wistar rats were divided into three groups: control (C), hypertensive (H), and exercised hypertensive (EH). Hypertension was induced by administration of 20 mg/kg of L-NAME for 7 days prior to experimental protocols. The resistance exercise protocol consisted of 10 sets of 10 repetitions and intensity of 40% of one repetition maximum. The reactivity of vascular smooth muscle was evaluated by concentration‑response curves to phenylephrine (PHEN), potassium chloride (KCl) and sodium nitroprusside (SNP). Results: Rats treated with L-NAME showed an increase (p < 0.001) in systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) compared to the initial period of induction. No difference in PHEN sensitivity was observed between groups H and EH. Acute resistance exercise reduced (p < 0.001) the contractile response induced by KCl at concentrations of 40 and 60 mM in group EH. Greater (p < 0.01) smooth muscle sensitivity to NPS was observed in group EH as compared to group H. Conclusion: One resistance exercise session reduces the contractile response induced by KCl in addition to increasing the sensitivity of smooth muscle to NO in mesenteric arteries of hypertensive rats.